Utilization of Electronic Nose to Detect Quality of Meat in the Beef Ribs section - Hananto, Bayu; Widiyanto, Didit; Raafi'udin, Ridwan (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2023)
This study analyzes the use of Electronic Nose (E-Nose) in detecting the quality of beef on the ribs. This experiment used a variety of gas sensors, and found a significant pattern related to rib meat quality. There are three sensors, namely MQ137, MQ5, and MQ6, which show the value is inversely proportional to the other sensors. An increase in the value of this sensor indicates a decrease in the quality of the ribs. Furthermore, MQ8 gave the highest score in the "Good" and "Excellent" categories, while MQ5 and MQ6 gave the highest score in the "Equal" and "Not Eligible" categories. The analysis revealed that E-Nose has the ability to recognize changes in aroma associated with changes in the quality of rib meat. These results show that E-Nose can provide objective and fast information about the quality of beef in the ribs, which can support the food industry in decision making and product quality control. Further research is needed to optimize the use of sensors and validate this technology in various storage conditions and types of beef.